2022
DOI: 10.3390/molecules27113629
|View full text |Cite
|
Sign up to set email alerts
|

Poria Acid, Triterpenoids Extracted from Poria cocos, Inhibits the Invasion and Metastasis of Gastric Cancer Cells

Abstract: Background: Poria cocos (P. cocos) is an important medicinal fungus in traditional Chinese medicine. Poria acid (PA), a triterpenoid compound, is an effective component of traditional Chinese medicine P. cocos. This experiment investigated the anti-gastric cancer biological activity of PA in vitro. Methods: The effect of PA on the viability of gastric cancer cells was detected by the thiazolyl blue (MTT) assay. Cell adhesion assays were used to detect changes in the adhesion of cells treated after PA (0, 20, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…As can be seen from Figure 4D, the SASA is a parameter used to describe the hydrophobicity of a protein, with higher SASA values indicating greater hydrophobicity of the protein. The SASA values of the four systems were mainly in the range of 320-350 nm 2 , with mean val-ues of 341.91, 335.39, 340.28, and 336.57 nm 2 , respectively, indicating good tightness.…”
Section: Results Of MD Simulation Experimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…As can be seen from Figure 4D, the SASA is a parameter used to describe the hydrophobicity of a protein, with higher SASA values indicating greater hydrophobicity of the protein. The SASA values of the four systems were mainly in the range of 320-350 nm 2 , with mean val-ues of 341.91, 335.39, 340.28, and 336.57 nm 2 , respectively, indicating good tightness.…”
Section: Results Of MD Simulation Experimentsmentioning
confidence: 95%
“…As a commonly used medicine, Poria Cum Radix Pini (PRP) has a very long history of use in traditional Chinese medicine [1,2]. Accumulated evidence has revealed that PRP contains various active components, mainly polysaccharides, triterpenoids, sterols, volatile oils, and proteins [3].…”
Section: Introductionmentioning
confidence: 99%
“…TS, WSP, and AP are the three major active ingredients in PC. For example, TS has been proven to exert potent pharmacological effects [ 3 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], such as anti-inflammatory, anti-tumor, and diuretic effects [ 6 , 7 , 8 ]. Polysaccharides have liver-protective, immune-boosting, and anti-aging effects [ 28 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the inhibition of EMT is a key factor in the treatment of GC. Wang et al [ 99 ] found that Poria acid can inhibit the EMT process by significantly increasing the expression of E-cadherin and inhibiting the expression of N-cadherin and Vimentin, thereby inhibiting the invasion and metastasis of GC cells. Babaodan (BBD) is a TCM compound that has been used in clinical treatment since the Ming Dynasty, (more than 400 years ago).…”
Section: Other Mechanisms Of Action In the Treatment Of Gcmentioning
confidence: 99%